2017
DOI: 10.3892/or.2017.5992
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-154 as a prognostic factor in bladder cancer inhibits cellular malignancy by targeting RSF1 and RUNX2

Abstract: Recent studies have demonstrated that microRNA-154 (miR-154) is involved in tumorigenesis, progression, invasion and metastasis in several types of human cancer. However, whether it plays a role in bladder cancer (BC) is unclear. The aim of the present study was to determine miR-154 levels in human BC tissues and investigate the correlation between miR-154 levels and clinicopathological characteristics as well as patient outcome. Using RT-qPCR, we found that the expression levels of miR-154 were significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 39 publications
5
29
1
Order By: Relevance
“…In the present study, we found marked downregulation of miR-154 in BCa tissues and cell lines, which was consistent with the results of a previous study (15). Moreover, a decreased miR-154 level was correlated with aggressive clinicopathological features, including advanced T stage, lymphatic invasion, and distant metastasis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we found marked downregulation of miR-154 in BCa tissues and cell lines, which was consistent with the results of a previous study (15). Moreover, a decreased miR-154 level was correlated with aggressive clinicopathological features, including advanced T stage, lymphatic invasion, and distant metastasis.…”
Section: Discussionsupporting
confidence: 93%
“…For example, miR-145 (8), miR-122 (9) and miR-31 (10) have been revealed to influence tumorigenesis, tumor proliferation, invasion and metastasis. Several studies have also revealed that miR-154 acts as a tumor suppressor in a wide variety of human cancers, including prostate (11), colorectal (12), breast (13), liver (14) and BCa (15). However, the role of miR-154 in BCa progression has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, the studies conducted by Zhao et al and Zhang et al demonstrated that miR-154 was downregulated in bladder cancer tissue samples and cell lines. 39 , 40 According to Zhao et al’s experiments, miR-154 acts as a prognostic factor and can suppress bladder cancer by directly targeting RSF1 and RUNX2. 40 In agreement, Zhang et al reported that miR-154 functions as a tumor suppressor in bladder cancer by directly targeting ATG7.…”
Section: Mir-154 and Genitourinary System Cancersmentioning
confidence: 99%
“…39 , 40 According to Zhao et al’s experiments, miR-154 acts as a prognostic factor and can suppress bladder cancer by directly targeting RSF1 and RUNX2. 40 In agreement, Zhang et al reported that miR-154 functions as a tumor suppressor in bladder cancer by directly targeting ATG7. 39 Investigating the role of miR-154 in cervical cancer, Wu et al, found that the decreased expression level of miR-154 was significantly associated with clinicopathological features including lymph node metastasis, vascular invasion, poor tumor differentiation, advanced FIGO stage, and short overall survival.…”
Section: Mir-154 and Genitourinary System Cancersmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are key regulators in post-transcriptional suppression. They are small non-coding RNAs, approximately 22 nucleotides in length 11 . Their aberrant expression has been recently used as novel biomarkers detected in the urine of BBC and NBBC patients 12 .…”
Section: Introductionmentioning
confidence: 99%